Synthesis of fused hydroxy dihydropyrroles and unexpected dihydropyrazine and dihydroquinoxaline derivatives based on heterocyclic ketene aminals. (6th December 2019) - Rezaei, Monireh; Bayat, Mohammad; Notash, Behrouz
Abstract: The one‐pot four‐component synthesis of highly functionalized fused hydroxyl dihydropyrroles and dihydropyrazines from readily available diamines, 1, 1‐bis (methylsulfanyl)‐2‐nitroethene, phenylglyoxal monohydrates, and C‐H acids have been developed. This strategy provides an efficient, catalyst‐free approach for easy access to various new hydroxyl‐dihydropyrrole and dihydropyrazine rings in good to high yields. The products were confirmed by 1 H and 13 C NMR, IR, mass, and X‐ray crystal structure analyses. Abstract :